2019
DOI: 10.1007/s11605-018-3862-2
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Extent of Liver Resection Among Patients with Neuroendocrine Liver Metastasis: an International Multi-institutional Study

Abstract: NAR was independently associated with a higher incidence of recurrence versus patients who undergo a formal anatomic hepatectomy among patients with NELM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 16 publications
0
5
0
2
Order By: Relevance
“…17 There is precedent for metastasectomy in different neoplasms, especially for liver metastases from colorectal or pancreatic neuroendocrine cancer. 36,37 However, recurrent PDAC is particularly difficult to manage surgically, as it typically is characterized by multifocal and destructive spread. Therefore, pulmonary metastasectomy remains a non-standard and individual treatment approach, for which appropriate selection of patients with favorable tumor biology is paramount.…”
Section: Discussionmentioning
confidence: 99%
“…17 There is precedent for metastasectomy in different neoplasms, especially for liver metastases from colorectal or pancreatic neuroendocrine cancer. 36,37 However, recurrent PDAC is particularly difficult to manage surgically, as it typically is characterized by multifocal and destructive spread. Therefore, pulmonary metastasectomy remains a non-standard and individual treatment approach, for which appropriate selection of patients with favorable tumor biology is paramount.…”
Section: Discussionmentioning
confidence: 99%
“…113,[118][119][120][121] Non-anatomic resection may be associated with a higher incidence of recurrence than formal anatomic hepatectomy, but has a similar impact on OS. 122 Surgical cytoreduction. For unresectable NET liver metastases, surgical cytoreduction can be considered.…”
Section: Surgical Management Of Liver Metastasismentioning
confidence: 99%
“…The benefit of surgical therapy of liver metastasis is discussed controversially. A recent analysis showed that the type of liver resection (anatomic versus non-anatomic) in patients with M1 disease showed higher rates of recurrence after non-anatomic resection but the type of resection did not affect overall survival [8]. Another analysis of 111 patients found that surgical resection influenced mortality after 5 but not after 10 years [9].…”
Section: Introductionmentioning
confidence: 99%